Chronic recurrent multifocal osteomyelitis exhibiting predominance of periosteal reaction - Queiroz,Rodolfo Mendes (2017)
Summary Chronic recurrent multifocal osteomyelitis is an idiopathic nonpyogenic autoinflammatory bone disorder involving multiple sites, with clinical progression persisting for more than 6 months and which may have episodes of remission and exacerbation in the long term. It represents up to 2-5% of the cases of osteomyelitis, with an approximate incidence of up to 4/1,000,000 individuals, and average age of disease onset estimated between 8-11 years, predominantly in females. The legs are the most affected, with a predilection for metaphyseal regions along the growth plate. We describe the case of a female patient, aged 2 years and 5 months, with involvement of the left ulna, right jaw and left tibia, showing a predominance of periosteal reaction as main finding.